Profile of the teachers participating in the second edition of the "Escola da Terra/Sergipe" Program - Tereza Simone Carvalho; Josefa de Lisboa (Universidade Federal do Norte do Tocantins, 2022)
The "Escola da Terra" Program is the only training policy for countryside educators in Sergipe that reached 160 teachers from 14 cities, in its second edition. The shortage of this training affects the development of a pedagogical practice consistent with the countryside education's principles and goals. Thus, this article aims to analyze the profile of the teachers of the second edition of the "Escola da Terra/Sergipe" program. Therefore, we carried out a diagnostic activity with the participants, through a questionnaire about countryside education, the Brazilian and Sergipe's countryside, and the countryside schools nucleation/shutdown. The data analyses led to the following results: most of the teachers do not know the history, the goals and the principles of the countryside education, nor the reality where they work, developing, consequently, a pedagogical practice that is distant from the subjects to whom it is intended; the group perceives the student's parents or legal guardians inability to keep up with the activities/exercises sent home as the biggest issue to the development of their teaching practice. In conclusion, it is noted that the participating teachers have an urban understanding of the countryside and develop a teaching practice that is similar to the rural education.